Plant diversity effects on soil microbial functions and enzymes are stronger than warming in a grassland experiment. Issue 1 (1st January 2015) - Steinauer, Katja; Tilman, David; Wragg, Peter D.; Cesarz, Simone; Cowles, Jane M.; Pritsch, Karin; Reich, Peter B.; Weisser, Wolfgang W.; Eisenhauer, Nico
Abstract : Anthropogenic changes in biodiversity and atmospheric temperature significantly influence ecosystem processes. However, little is known about potential interactive effects of plant diversity and warming on essential ecosystem properties, such as soil microbial functions and element cycling. We studied the effects of orthogonal manipulations of plant diversity (one, four, and 16 species) and warming (ambient, +1.5°C, and +3°C) on soil microbial biomass, respiration, growth after nutrient additions, and activities of extracellular enzymes in 2011 and 2012 in the BAC (biodiversity and climate) perennial grassland experiment site at Cedar Creek, Minnesota, USA. Focal enzymes are involved in essential biogeochemical processes of the carbon, nitrogen, and phosphorus cycles. Soil microbial biomass and some enzyme activities involved in the C and N cycle increased significantly with increasing plant diversity in both years. In addition, 16‐species mixtures buffered warming induced reductions in topsoil water content. We found no interactive effects of plant diversity and warming on soil microbial biomass and growth rates. However, the activity of several enzymes (1, 4‐β‐glucosidase, 1, 4‐β‐N‐acetylglucosaminidase, phosphatase, peroxidase) depended on interactions between plant diversity and warming with elevated activities of enzymes involved in the C, N, and P cycles at both high plant diversity and high warming levels. Increasing plant diversity consistently decreased microbial biomass‐specific enzyme activities and altered soil microbial growth responses to nutrient additions, indicating that plant diversity changed nutrient limitations and/or microbial community composition. In contrast to our expectations, higher plant diversity only buffered temperature effects on soil water content, but not on microbial functions. Temperature effects on some soil enzymes were greatest at high plant diversity. In total, our results suggest that the fundamental temperature ranges of soil microbial communities may be sufficiently broad to buffer their functioning against changes in temperature and that plant diversity may be a dominant control of soil microbial processes in a changing world.